2018
DOI: 10.1038/s41401-018-0066-y
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane postconditioning protects against myocardial ischemia/reperfusion injury by restoring autophagic flux via an NO-dependent mechanism

Abstract: Volatile anesthetics improve postischemic cardiac function and reduce infarction even when administered for only a brief time at the onset of reperfusion. A recent study showed that sevoflurane postconditioning (SPC) attenuated myocardial reperfusion injury, but the underlying mechanisms remain unclear. In this study, we examined the effects of sevoflurane on nitric oxide (NO) release and autophagic flux during the myocardial ischemia/reperfusion (I/R) injury in rats in vivo and ex vivo. Male rats were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…From clinical practice, SPostC is easier to control than ischemic postconditioning and can exert similar myocardial protective effects as ischemic postconditioning Li et al, 2008). Studies have shown that in non-diabetic conditions, SPostC promotes autophagic flux against myocardial ischemia-reperfusion injury through a NO-dependent mechanism, but the effect of SPostC on mitochondrial autophagy and related receptors was not mentioned (Qiao et al, 2019). Zhang et al found that SPostC promoted autophagic flow against myocardial I/RI by reducing the accumulation of autophagosomes, but the role of signaling pathways that mediate autophagy was not discussed further (Zhang et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From clinical practice, SPostC is easier to control than ischemic postconditioning and can exert similar myocardial protective effects as ischemic postconditioning Li et al, 2008). Studies have shown that in non-diabetic conditions, SPostC promotes autophagic flux against myocardial ischemia-reperfusion injury through a NO-dependent mechanism, but the effect of SPostC on mitochondrial autophagy and related receptors was not mentioned (Qiao et al, 2019). Zhang et al found that SPostC promoted autophagic flow against myocardial I/RI by reducing the accumulation of autophagosomes, but the role of signaling pathways that mediate autophagy was not discussed further (Zhang et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane is an inhaled volatile anaesthetic that is widely used in clinical and basic research due to its pharmacological characteristics such as induction of stability and rapid recovery. Many studies have confirmed that sevoflurane postconditioning (SPostC) can alleviate ischemia-reperfusion injury effectively in healthy myocardium (Yu et al, 2015;Wu et al, 2017b;Qiao et al, 2019). However, in the diabetic state, myocardial protection of SPostC is weakened (Drenger et al, 2011;Tai et al, 2012;Gao et al, 2016), and the specific mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…So even they will provide the trial intervention, but they will not be involved in either the postoperative treatment or the analysis. Secondly, since the inhaled anesthetic sevoflurane is considered to be significantly cardioprotective and the high-dose propofol has also been reported to have a certain myocardial protective effect [ 27 29 ], both of which are currently widely used in clinical anesthetics, how to reduce their interference on the results of intralipid postconditioning is of great importance. In our previous pilot study [ 18 , 19 ], all included patients were given total intravenous anesthesia to eliminate the interference of sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, since the inhaled anesthetic sevoflurane is considered to be significantly cardioprotective and the high-dose propofol has also been reported to have a certain myocardial protective effect [26][27][28], both of which are currently widely used in clinical anesthetics, how to reduce their interference on the results of intralipid postconditioning is of great importance. In our previous pilot study [18,19], all included patients were given total intravenous anesthesia to eliminate the interference of sevoflurane.…”
Section: Discussionmentioning
confidence: 99%